2015
DOI: 10.1007/s10562-015-1584-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Redox Properties of Bulk Vanadium Mixed Oxide Catalysts

Abstract: A series of bulk vanadium mixed oxides (Ce, Al, Fe or Cr) were successfully prepared. Methanol and propane were proposed as probe molecules to investigate the redox properties of this series of bulk vanadium mixed oxides and a qualitative picture of the redox properties was obtained. Specifically, we tested steady-state methanol oxidation at range 250-300°C and oxidative dehydrogenation (ODH) of propane to propene at range 350-550°C. We also explored the turn over frequency of redox products (TOF redox ) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Raman spectra collected at room temperature is shown in Figure 4. The Raman spectra of BiVO 4 , CrVO 4 , FeVO 4 , and Co 2 V 2 O 7 were in agreement with literature [10,20,22,23] and the spectra did not show the characteristic bands of V 2 O 5 . Hence, no effort was taken to consider the product selectivity in this work.…”
Section: Thermal Expansion Propertysupporting
confidence: 88%
“…Raman spectra collected at room temperature is shown in Figure 4. The Raman spectra of BiVO 4 , CrVO 4 , FeVO 4 , and Co 2 V 2 O 7 were in agreement with literature [10,20,22,23] and the spectra did not show the characteristic bands of V 2 O 5 . Hence, no effort was taken to consider the product selectivity in this work.…”
Section: Thermal Expansion Propertysupporting
confidence: 88%
“…The formation of the two characteristic peaks at 214 and 319 cm −1 can be caused by the elastic vibrations of the nonequivalent O─Fe bond. [23] 88 and 135 cm −1 can be devoted to the bending vibrations of the FeVO 4 polyhedra. It can also be seen that there are no characteristic peaks at 1000-1024 cm −1 , so the FeVO 4 samples synthesized at pH of 2 and 3 can be excluded from containing V 2 O 5 impurities, and there are no obvious 𝛼-Fe 2 O 3 phase characteristic peaks formed, indicating that the prepared samples are pure.…”
Section: Morphology and Structure Of Fevo 4 Samplesmentioning
confidence: 99%
“…Several metal oxides, including supported vanadium oxides catalysts, have been studied for methanol oxidation [4,[36][37][38][39]. In addition, a comparison between catalytic performance for oxidation of methanol [39][40][41][42][43] or ethanol [44] and propane ODH has been reported in the last years. More recently, it has been reported that the use of methanol adsorption/desorption followed by in situ DRIFTS could be of interest in order to determine the concentration of active sites in Nb-doped nickel oxide catalysts, which are very selective in the ethane ODH [29].…”
Section: Introductionmentioning
confidence: 99%